Relationship between Financial Literacy and Behavior of Small Borrowers - Chaulagain, Ramesh Prasad (NRB Economic Review, 2017)
Financial literacy is an emerging and common concept both of education and finance. In general, the concept is important for every ones who has to manage the money; the concept plays vital role for low income people and small borrowers in particular. The small borrowers are those who borrow a limited amount of money from the licensed financial institutions. The borrowers are small on the basis of their credit limits determined by Nepal Rastra Bank. In this study, financial literacy, as one of the significant factors to determine the financial behavior of small borrowers, was measured to establish the relationship to each other. In this paper, the level of financial literacy of small borrowers was compared with their financial attitude and behavior, for which data were collected from survey of small borrowers of two cooperatives licensed by Nepal Rastra Bank. Chi-square test was applied to test the hypothesis that showed the relationship between these selected variables. The analysis showed that the relationship of financial literacy of small borrowers was significant with their financial attitude and behavior. Hence, we argue that that there is a need of a systematic enhancement of financial literacy of the small borrowers to change their attitude and thereby the financial behavior.